2005
DOI: 10.1007/bf03393016
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Palilalia by Presenting Tact Corrections to Young Children with Autism

Abstract: Palilalia, the delayed repetition of words or phrases, occurs frequently among individuals with autism and developmental disabilities. The current study used a combined multiple baseline and reversal design to investigate the effectiveness of presenting tacts as corrections for palilalia. During baseline, five preschoolers with autism emitted high rates of palilalia and low rates of mands and tacts during play and instructional activities. During treatment, when experimenters presented opportunities to echoica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 11 publications
3
47
0
Order By: Relevance
“…Tourette's syndrome, acquired aphasias), but which has not been generally discussed in relation to ASD. An exception is Karmali (2000), who identifies four young children exhibiting both palilalia and 'characteristics of autism'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tourette's syndrome, acquired aphasias), but which has not been generally discussed in relation to ASD. An exception is Karmali (2000), who identifies four young children exhibiting both palilalia and 'characteristics of autism'.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that repeated talk provides resources for both impaired speakers and those interacting with them has underpinned the handful of CA case studies of children with an ASD. Local and Wootton (1995) note that 'unusual echoes' are routinely treated by a co-participating adult as non-meaningful. Despite this, they show that the child's ('Kevin') co-participants used forms of turn design which encouraged the child to produce repeats of the utterance.…”
Section: Introductionmentioning
confidence: 99%
“…Research based on Skinner's (1957) theory has proliferated in recent years and has contributed to the identification of procedures for inducing verbal operants in children who are missing them. Much of this experimentation has focused on the dependence and interdependence of the classes of verbal repertoires (Becker, 1989;Greer, Nuzzolo-Gomez, Ross, & Rivera-Valdez, 2005;Lamarre & Holland, 1985;Lodhi & Greer, 1989;Michael, 1982;Twyman, 1996aTwyman, , 1996bYoon, 1998), the variables that functionally control verbal operants (Chu, 1998;Karmali, Greer, Nuzzolo-Gomez, Ross, & Rivera-Valdes, 2005;Ross & Greer, 2003;Sundberg, Michael, Partington, & Sundberg, 1996;Tsiouri & Greer, 2003;Williams & Greer, 1993), and studies testing several theoretical explanations for, and the source of, productive verbal repertoires (Greer & Keohane, 2005;Greer & Ross, 2004;Greer, Stolfi, Chavez-Brown, & Rivera-Valdez, 2005;Greer, Yuan, & Gautreaux, 2005;Horne & Lowe, 1996;Ross & Greer, 2003). One source of verbal behavior that has been identified in the literature is naming.…”
mentioning
confidence: 99%
“…Other research has shown that there are effective tactics to increase "on task" academic behaviors involving self-management (Callahan & Rademacher, 1999;Stahmer & Schreibman, 1992), the reduction of inappropriate behavior (Tasky, Rudrud, Schulze, & Rapp, 2008;Machlicek, O'Reilly, Beretvas, Sigafoos, & Lancioni, 2007), and improvements in verbal behavior and reducing palalalia behaviors in children with autism and behavior disorders (Greer & Ross, 2008;Karmali, Greer, Nuzzolo-Gomez, Ross, & Valdes, 2005;Mancina, Tankersley, Kamps, Kravits, & Parrett, 2000). Conroy, Asmus, Sellers, & Ladwig (2005) successfully taught a six-year-old boy to discriminate times in the day at school where stereotypic behaviors were acceptable and not acceptable using an antecedent based intervention involving visual cuecards.…”
Section: Student and Settingmentioning
confidence: 99%